Pengaruh Karakteristik Pekerjaan, Rancangan Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai pada Badan Narkotika Nasional Kota Binjai - Mendrofa, Rio Anugrah; Hasibuan, Hasrul Azwar (Universitas Negeri Medan, 2025)
This study aims to test and determine the influence of work characteristics, work design, organizationalculture and employee performance of the National Narcotics Office of Binjai City. The method used is aquantitative approach with the help of the SPSS application. This study uses multiple linear regression analysis.The sample in this study was 36 respondents. Primary data collection uses questionnaires. And the results of thisstudy show that the characteristics, work design and organizational culture have a positive and significant effecton the performance of employees of the Binjai City National Narcotics Agency Office..